Solder joint fatigue in a surface mount assembly subjected to mechanical loading - Tamin, M. N.; Liew, Y. B.; Wagiman, A. N. R.; Loh, W. K. (Institute of Electrical and Electronics Engineers, 2007)
A mechanical approach employing cyclic twisting deformation to a surface mount assembly is examined as an alternative to temperature cycling for evaluating solder joints fatigue performance. This highly accelerated test is aimed at reducing solder joint reliability testing cycle time. In this study, the mechanics of solder joints in a surface mount assembly subjected to cyclic twisting deformation is investigated. For this purpose, a test package with 24 by 24 peripheral-array solder joints is modeled using the finite element method. Unified inelastic strain theory defines the strain-rate-dependent plastic stress-strain response of the 60 Sn-40 Pb solder. Cyclic twisting deformation in the range of ±1° per 50 mm length of the assembly board at a rate of 120 s per twist cycle was applied. The calculated stress and strain distributions in the critical solder joint are compared with those predicted for temperature cycling and accelerated temperature cycling tests. Results showed that the accumulated inelastic strain concentrates in a small region of the critical solder joint near the component side for temperature cycling and near the board side for cyclic twisting load cases. The rate of inelastic strain accumulation per fatigue cycle in the solder joint for both temperature cycling (TC1) and mechanical twisting (MT1) tests are similar. Thus, mechanical twisting test imparts similar deformation characteristics to temperature cycling tests in terms of the shear strain range. Low cycle fatigue is dominated by localized shear effect as reflected in the largest shear strain range of the hysteresis loops. The Coffin-Manson strain-based model yielded more conservative prediction of fatigue lives of solder joints when compared to energy-based approach. © 2007 IEEE.